О тематической парадигме «Термины родства» монгольского и русского языков: On the thematic paradigms "Terms of kinship" in the Mongolian and Russian languages - Д.Л. , Шагдарова (Mongolian Studies, 2023)
There are thematic groups of words, which identify same appearance of reality and from the aspects meaning, function and relationship are common in the Mongolian, Buryat and Russian languages. Kinship terms in the Mongolian and Russian languages are quite extensive thematic paradigm. As known, the terminology of kinship includes two groups of lexemes: terms of blood and non-blood kinship.